Dei delitti e delle pene nella traduzione di Michail M. Scerbatov - GHERBEZZA, Ettore (Biblioteca di Studi Slavistici, 2007)
After more than two centuries, this work presents the Russian version of "Dei delitti e delle pene" by Cesare Beccaria, translated by Prince Michail M. Šcerbatov. The edition, conducted on the autographed manuscript, is presented with the original Italian text. In the introductory study, the author traces the fundamental stages of the diffusion of Beccaria's work in Russia, focusing in particular on the figure of Michail M. Isaev, scholar and translator of the masterpiece by Beccaria, who was the first to re-propose the modern organisation of the "Fifth" edition. The author gives an account of the version proposed by Šcerbatov, investigating its textual genesis and evaluating some aspects of the language used by the translator - first of all the lexicon used for the rendering of philosophical-political and legal terms.